2016
DOI: 10.1038/eye.2016.273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of Ahmed glaucoma valve in anterior chamber versus ciliary sulcus

Abstract: PurposeTo evaluate the outcomes of Ahmed glaucoma valve (AGV) tube insertion through the anterior chamber angle (ACA) or through the ciliary sulcus (CS).Patients and methodsIn this case-control study, we retrospectively reviewed the charts of consecutive glaucoma patients who had undergone AGV implantation either through the ACA or the CS between March 2009 and December 2014. The main outcome measures were intraocular pressure (IOP), number of glaucoma medications prescribed, best corrected visual acuity (BCVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 25 publications
1
34
1
Order By: Relevance
“…In the literature, hyphema has been reported to occur in 8% to 16.9% of patients after implantation of the AGV tube in the anterior chamber angle or pars plana (18)(19)(20)(21). In their study of AGV tube implantation in the ciliary sulcus, Bayer et al (10) found a ratio of hyphema of 14.3%. The greater vascularization of the ciliary sulcus compared with the anterior chamber angle or pars plana may have contributed to these findings (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, hyphema has been reported to occur in 8% to 16.9% of patients after implantation of the AGV tube in the anterior chamber angle or pars plana (18)(19)(20)(21). In their study of AGV tube implantation in the ciliary sulcus, Bayer et al (10) found a ratio of hyphema of 14.3%. The greater vascularization of the ciliary sulcus compared with the anterior chamber angle or pars plana may have contributed to these findings (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a rate of between 7% and 27% (6)(7)(8)(9). Tube implantation into the pars plana or ciliary sulcus has been investigated as a possible means of reducing contact in cases with a risk of corneal decompensation or peripheral anterior synechiae (PAS) (4,(10)(11)(12). AGV insertion into the ciliary sulcus has been proposed as a more advantageous option because AGV insertion into the pars plana is thought to be associated with more posterior segment complications and more additional inflammation following vitrectomy (13).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this technique may not only be used to treat tube exposure but may also be considered during primary implantation to avoid any future tube exposure. In a paper comparing outcomes of Ahmed GDD with tube insertion in the AC versus the CS, tube/plate exposure was reported in 2.9% in the AC group, compared to 0% in the CS group [20]. Although this difference did not reach statistical significance due to a limited sample size, it suggests a trend towards decreased exposure with posterior insertion.…”
Section: Case Reports In Ophthalmological Medicinementioning
confidence: 97%
“…Insertion of GDD tubes in the CS has been shown to be safe and effective in the past [18][19][20][21]. In fact, this technique may not only be used to treat tube exposure but may also be considered during primary implantation to avoid any future tube exposure.…”
Section: Case Reports In Ophthalmological Medicinementioning
confidence: 99%
“…Recent studies have shown that tube implantation through the ciliary sulcus is safe and efficacious for the Ahmed and Baerveldt GDDs. [ 15 16 17 18 19 20 ] Two of these studies describe a similar technique which requires an inferotemporal paracentesis with placement of viscoelastic superiorly to inflate the sulcus. [ 14 19 ] These studies report a 26–28% risk of early postoperative hyphema and 8–9% risk of flat/shallow anterior chamber complications, both of which may place the corneal endothelium at risk for further injury.…”
Section: Introductionmentioning
confidence: 99%